Social achievement, social status, and self esteem - Faunce, William A. (American Sociological Association, 1984)
The primary focus of this study is upon variation in the effect of status upon self-esteem. Data were collected through interviews with the senior class of a Michigan high school. The findings indicate that academic, achievement had an important impact upon status in this senior class. The effect of academic achievement upon self-esteem, however, appeared to vary depending upon patterns of association with other students and upon the values that could be inferred as the bases for status placement in different networks. The general conclusions is that being well informed about one's location in a status hierarchy does not necessarily have the same consequences as being frequently reminded of that location. This evidence supports the idea that our conception of self, and consequently, our degree of concern for achievement in various areas, is anchored primarily in on-going social relationships in recurring social settings.